Genomic Programming of Human Neonatal Dendritic Cells in Congenital Systemic and In Vitro Cytomegalovirus Infection Reveal Plastic and Robust Immune Pathway Biology Responses - Dantoft, Widad; Martínez-Vicente, Pablo; Jafali, James; Pérez-Martínez, Lara; Martin, Kim; Kotzamanis, Konstantinos; Craigon, Marie; Auer, Manfred; Young, Neil T.; Walsh, Paul; Marchant, Arnaud; Angulo, Ana; et al. (Frontiers in Immunology, 2017)
Neonates and especially premature infants are highly susceptible to infection but still can have a remarkable resilience that is poorly understood. The view that neonates have an incomplete or deficient immune system is changing. Human neonatal studies are challenging and elucidating host protective responses and underlying cognate pathway biology, in the context of viral infection in early life, remains to be fully explored. In both resource rich and poor settings human cytomegalovirus (HCMV) is the most common cause of congenital infection. By using unbiased systems analyses of transcriptomic resources for HCMV neonatal infection, we find the systemic response of a pre-term congenital HCMV infection, involves a focused IFN regulatory response associated with dendritic-cells. Further analysis of transcriptional-programming of neonatal dendritic cells in response to HCMV infection in culture revealed an early dominant IFN-chemokine regulatory sub-networks, and at later times the plasticity of pathways implicated in cell-cycle control and lipid metabolism. Further, we identify previously unknown suppressed networks associated with infection, including a select group of GPCRs. Functional siRNA viral-growth screen targeting 516-GPCRs and subsequent validation identifies novel GPCR-dependent antiviral (ADORA1) and proviral (GPR146, RGS16, PTAFR, SCTR, GPR84, GPR85, NMUR2, FZ10, RDS, CCL17, and SORT1) roles. By contrast a gene family cluster of protocadherins is significantly differentially induced in neonatal cells, suggestive of possible immune-modulatory roles. Unexpectedly, programming responses of adult and neonatal dendritic cells, upon HCMV infection, demonstrated comparable quantitative and qualitative responses showing that functionally, neonatal dendritic cell are not overly compromised. A delay in responses of neonatal cells for IFN sub-networks in comparison with adult derived cells are notable, suggestive of subtle plasticity differences. These findings support a set-point control mechanism rather than immaturity for explaining not only neonatal susceptibility but also resilience to infection. In summary, our findings show that neonatal HCMV infection leads to a highly plastic and functional robust programming of dendritic cells in vivo and in vitro, although in comparison with adults, a small number of subtle quantitative and temporal differences may contribute to variability in responses that, in a context dependent manner, affect host susceptibility and resilience.